2020
DOI: 10.1590/2236-8906-01/2020
|View full text |Cite
|
Sign up to set email alerts
|

Respiração de embriões recalcitrantes de Inga vera Willd. subsp. affinis (DC.) T.D. Pennington sob diferentes temperaturas, potenciais osmóticos e aplicação de ABA

Abstract: RESUMO O elevado metabolismo de sementes sensíveis à dessecação (recalcitrantes) de Inga vera Willd. subsp. affinis (DC.) T.D.Pennington é um dos principais fatores que dificultam a manutenção da viabilidade fisiológica das sementes durante o armazenamento. Devido à falta de informações sobre o metabolismo respiratório dessas sementes em diferentes condições de estresse, este estudo teve como objetivo determinar as taxas de respiração de embriões com diferentes conteúdos de água e em diferentes temperaturas ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Therefore, these (PIR) are embryos at a more advanced stage of maturation than those of SAP and PAR and are very similar to those of RIB. Thus, it was clear that environmental conditions had an important effect on the maturation process of Inga vera seeds until the moment of dispersion, as reported in previous works, also for other species of the same genus (Bonjovani and Barbedo, 2020;Mata et al, 2013).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, these (PIR) are embryos at a more advanced stage of maturation than those of SAP and PAR and are very similar to those of RIB. Thus, it was clear that environmental conditions had an important effect on the maturation process of Inga vera seeds until the moment of dispersion, as reported in previous works, also for other species of the same genus (Bonjovani and Barbedo, 2020;Mata et al, 2013).…”
Section: Resultssupporting
confidence: 77%
“…The results of the initial characterization showed that, although all the fruits had been collected when they were ripe, their embryos showed maturation differences: those of RIB, for example, were closer to physiological maturity than the others, because: a) although the embryos from all regions had very high water content, above 50%, typical for species of the genus Inga (Mata et al, 2013;Schulz et al, 2014), those from RIB had the lowest water potential. This result indicates more binding sites, therefore a better structured matrix (Vertucci and Farrant, 1995); b) the embryos accumulated more dry weight (Marcos-Filho, 2015); c) they had a lower respiration rate, indicating that they were among more mature embryos (the more mature, the lower the respiratory rate, Araujo and Barbedo, 2017) and embryos that had already started germination (the more advanced in germination, the higher the respiratory rates, Hell et al, 2019); d) they had the longest mean germination time, indicating that they had not started germination before harvest, which is relatively common for embryos of this species (Andreo et al, 2006;Bonjovani and Barbedo, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pennington embryos were obtained at Villa-Lobos Park (23°32' S; 46°43' W), São Paulo, SP, Brazil. Fruits were harvested manually when ripe, as described by Bonjovani and Barbedo (2020) and then taken to the Seed Analysis Laboratory, where their diaspores (embryos and sarcotesta) were extracted and washed. The sarcotesta was removed and the embryos were then washed under running water to remove any residues of sugars, which could compromise their storage.…”
Section: Incubation Of Embryos In Masmentioning
confidence: 99%
“…Thus, the objective of this study was to develop methods that allow the generation of MAs in a standardizable way, thus, allowing analyzing the reduction of respiratory metabolism of recalcitrant seeds. Subsequently, recalcitrant embryos of Inga vera, considered to be among the most recalcitrant known (Bonjovani and Barbedo, 2020;Pereira et al, 2020), were used as a model for controlling this respiration, seeking atmospheres that reduce the respiratory rates of these embryos during storage.…”
Section: Introductionmentioning
confidence: 99%